Burden of Diabetes Mellitus and Its Determinants among Adults (≥30 Years) Residing in Urban Field Practice Area of A Tertiary Care Teaching Hospital, Uttar Dinajpur, West Bengal - Nabarun Mandal; Debayan Podder; Nazrul Mallick; Puspendu Biswas (Acta Medica International)
Introduction: Diabetes mellitus (DM) poses a significant global health challenge, particularly in countries like India. Despite the multitude of studies, relatively few have assessed the burden of diabetes and its determinants in a resource-limited district in West Bengal, India, utilizing various biochemical and anthropometric parameters. Materials and Methods: The cross-sectional study was conducted from July to December 2023 to assess the burden of diabetes and its determinants among an estimated sample of 114 adults (≥30 years) residing in the urban field practice area of tertiary care hospital in Uttar Dinajpur, West Bengal. Sociodemographic and behavioral data were collected through household survey using a predesigned, pretested interview schedule, whereas the anthropometric and biochemical data were collected on prefixed days at the urban primary health center using standardized tools and techniques as appropriate. Data were analyzed with SPSS version 20 using descriptive and inferential statistics. Univariate and multivariable logistic regression was performed to identify associations between diabetes and its determinants. Results: Prevalence of DM and prediabetes was 39.47% and 31.58%, respectively. Factors significantly associated with DM were female (adjusted odd ratio [AOR] = 4.55, 95% confidence interval [CI] [1.06–19.41]), overweight participants (AOR = 6.53, 95% CI [1.02–41.85]), physical activity (AOR = 2.83, 95% CI [1.05–7.65]), and family history of diabetes (AOR = 2.74, 95% CI [1.04–7.22]). Conclusion: The findings underscore the urgent need for implementation of targeted public health interventions aimed at reducing the prevalence of diabetes and mitigating its associated risks at national and subnational level.